Mammalian Comparative Genomics Reveals Genetic and Epigenetic Features Associated with Genome Reshuffling in Rodentia - Capilla, Laia (Genome Biol Evol, 2016)
Understanding how mammalian genomes have been reshuffled through structural changes is fundamental to the dynamics of its composition, evolutionary relationships between species and, in the long run, speciation. In this work, we reveal the evolutionary genomic landscape in Rodentia, the most diverse and speciose mammalian order, by whole-genome comparisons of six rodent species and six representative outgroup mammalian species. The reconstruction of the evolutionary breakpoint regions across rodent phylogeny shows an increased rate of genome reshuffling that is approximately two orders of magnitude greater than in other mammalian species here considered. We identified novel lineage and clade-specific breakpoint regions within Rodentia and analyzed their gene content, recombination rates and their relationship with constitutive lamina genomic associated domains, DNase I hypersensitivity sites and chromatin modifications. We detected an accumulation of protein-coding genes in evolutionary breakpoint regions, especially genes implicated in reproduction and pheromone detection and mating. Moreover, we found an association of the evolutionary breakpoint regions with active chromatin state landscapes, most probably related to gene enrichment. Our results have two important implications for understanding the mechanisms that govern and constrain mammalian genome evolution. The first is that the presence of genes related to species-specific phenotypes in evolutionary breakpoint regions reinforces the adaptive value of genome reshuffling. Second, that chromatin conformation, an aspect that has been often overlooked in comparative genomic studies, might play a role in modeling the genomic distribution of evolutionary breakpoints.